Pengaruh Citra Merek, Harga, dan Kualitas Produk Terhadap Loyalitas Konsumen iPhone pada Mahasiswa YKPN Yogyakarta - Brian Putra Bagaskara; Any Agus Kana (Cakrawangsa Bisnis: Jurnal Ilmiah Mahasiswa, 2021)
Abstract Research and development in the field of information technology has created an outstanding product that can improve the quality of human life..One type of goods produced is a mobile communication product. Smartphones are one of the most requested items in the Industrial Era 4.0. The high demand for smartphones has prompted several companies to produce them, one of which is Apple Inc. producing iPhones.iPhone is one of the famous smartphone brands among Indonesian students including at Yayasan Keluarga Pahlawan Negara (YKPN) Yogyakarta.This study aims to analyze the influence of brand image, price and product quality on the loyalty of iPhone smartphone consumers to YKPN Yogyakarta students. This research is quantitative research.The data was collected from 102 respondents using questionnaires through Google form.. The results of validity and reliability tests on research instruments are declared valid and reliable.The test results of normality, multicolerity and heteroskedastisity against multiple linear regression models all meet the requirements.The results showed that brand image, price students. Adjusted R2 shows that brand image, price and product quality influenced by 44% on consumer loyalty the remaining 56% was explained by other variables not included in the study.